(untitled) (JEELT : JOURNAL OF EDUCATION AND ENGLISH LANGUAGE TEACHING, 2023)
This research was conducted with the aim of finding out how the listen-read-discuss strategy can improve students’ reading comprehension of descriptive text. This research was conducted using classroom action research. Researcher conducted research at SMPN 03 Mempawah Hilir and the subjects in this research were class VIII B consisting of 22 students. For data collection, researcher used field notes and reading tests to find out whether there was progress in improving students’ reading comprehension in descriptive text. This research was conducted in two cycles, in cycle 1 the average student score was 65 and it was categorized as low or unsatisfactory. Then, the researcher continued to cycle 2 using classroom action research. The researcher focused more on attracting students’ attention to focus on learning and asking students to remember difficult words in descriptive texts. Therefore, in cycle 2 the students’ average score increased to 87,3 and it was in the good category. This shows that there is an increase in students’ scores in improving their reading comprehension of descriptive texts after implementing the listen-read-discuss strategy in the classroom learning process. As a result of this research, it can be concluded that there has been an increase in students’ reading comprehension in descriptive text. Student involvement during the implementation of descriptive text reading comprehension went well and was satisfactory. The application of the listen-read-discuss strategy succeeded in helping students to improve their reading comprehension of descriptive texts and understand new vocabulary well. In conclusion, students can improve reading comprehension in descriptive texts through implementing the listen-read-discuss strategy.